The Oxidative Cross-Coupling of Benzonitriles with Multiform Substrates: A Domino Strategy Inspired Easy Access to α-Ketoimides - Kalmode, Hanuman P.; Vadagaonkar, Kamlesh S.; Chaskar, Atul C. (Synthesis, 2015)
An iodine-promoted highly efficient convergent synthesis of α-ketoimides from multiform substrates and benzonitriles through oxidative imidation reaction is described. This domino oxidative imidation process involves cleavage of C–H bond and construction of C–O and C–N bonds. This method could be a powerful compliment to the existing methods owing to its use of abundantly available starting materials and reagents.
Keywords: iodine; metal-free synthesis; Kornblum oxidation; α-ketoimides; multiform substrates